2004
DOI: 10.1074/jbc.m403730200
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Scrapie and Bovine Spongiform Encephalopathy Isolates by Infrared Spectroscopy of Pathological Prion Protein

Abstract: For the surveillance of transmissible spongiform encephalopathies (TSEs) in animals and humans, the discrimination of different TSE strains causing scrapie, BSE, or Creutzfeldt-Jakob disease constitutes a substantial challenge. We addressed this problem by Fourier transform-infrared (FT-IR) spectroscopy of pathological prion protein PrP27-30. Different isolates of hamsteradapted scrapie (263K, 22A-H, and ME7-H) and BSE (BSE-H) were passaged in Syrian hamsters. Two of these agents, 22A-H and ME7-H, caused TSEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 46 publications
8
63
0
Order By: Relevance
“…In the past several years considerable evidence has accumulated indicating that prion strains do, indeed, exhibit notable differences in the amount and type of ␤-sheet structure, conformational stability, proteolytic resistance, and surface-exposed epitopes (2)(3)(4)(5)(6)(7). Although the results of these aforementioned studies were consistent with the protein-only hypothesis, the primary origin of strain-specific conformational variations remains unclear.…”
supporting
confidence: 61%
“…In the past several years considerable evidence has accumulated indicating that prion strains do, indeed, exhibit notable differences in the amount and type of ␤-sheet structure, conformational stability, proteolytic resistance, and surface-exposed epitopes (2)(3)(4)(5)(6)(7). Although the results of these aforementioned studies were consistent with the protein-only hypothesis, the primary origin of strain-specific conformational variations remains unclear.…”
supporting
confidence: 61%
“…This preferential involvement of rostral brain regions in L-type BSE has also been described in cattle ( 13 ) and on transmission into bovine transgenic mice ( 18 , 24 ). Transmission of TME or typical BSE into wild-type mice ( 31 , 32 ) or hamsters ( 33 , 34 ) also resulted in distinct transmissibility between these TSEs in these host species. Based on these findings, we conclude that typical BSE is not a likely source for TME in mink; however, if TME were to be due to infection with a cattle TSE, the most likely candidate is L-type BSE.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that this approach is sensitive and specific (97% and 100% respectively) but it was not known whether the changes detected by FTIR were specific to TSEs or whether they were due to bacterial, viral, fungal or parasitic micro-organisms. Analysis by FTIR has proved useful for discriminating between scrapie and BSE pathological PrP strains [112], identifying protein structural changes in nerve ganglia of infected hamsters [56], and brain tissue of TSE infected animals [54,55].…”
Section: Mid-infrared Spectroscopymentioning
confidence: 99%